Impact of Air Pollution on Health: A Neighbourhood Level Study Led by Grassroot Women Leaders in Rural Jharkhand, India - Shrivastava, Saumya; Saigal, Neha (The Canadian Journal of Action Research, 2025)
Jharkhand state in India has high levels of air pollution posing severe health and environmental hazards especially in mining districts. Ten grassroots women leaders undertook community-participatory research to track air quality in their neighbourhoods. Through this research, they assessed people’s perceptions on neighbourhood sources of air pollution, health impacts and responsiveness of the government health system to ailments linked to that air pollution. Their findings reveal poor air quality in places frequented by women, children, and vulnerable populations and further highlights adverse health impacts and the inadequate capacity of the government health system. This research enabled the women to initiate dialogues with different stakeholders on severity of the issue and corrective action needed, leading to initiation of measures to tackle air pollution at the neighbourhood level.